THE ROLE OF SCIENTIFICALLY SUBSTANTIATED PREDICTION IN THE RECOGNITION OF A TOURIST DESTINATION: (on the example of the Republic of Armenia) (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
Prediction of the tourist demand can be carried out through the usage of regression model. There have been surveys conducted among tourists (non-ethnic Armenians) who have visited Armenia over the past 3 years. It was necessary to find out whether the gender and age composition of potential tourists influences the choice of a particular media channel, as well as to identify those media channels that, having a certain potential, can influence the picture of the tourism market of Armenia. Based on the compiled model, it is possible to come to conclusions: the indicators of the regression model make it possible to navigate quite clearly by age groups.
Keywords: regression model; scientific based prediction; media; marketing steps; statistical forecasting; tourist destination